HAKIKAT DAN RUANG LINGKUP FILSAFAT ILMU - Rega Rahayu; Sisca Yuliasary; Desinta Rasyani; Retno Wahyu Ningsih; Saukani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The philosophy of science plays a fundamental role in forming a critical, systemic, and ethical framework for educational management. This study aims to analyze the nature and scope of the philosophy of science within the context of educational management, specifically focusing on the dimensions of ontology, epistemology, and axiology. The research utilizes a literature review methodology, examining various academic sources published between 2023 and 2026 accessed via Google Scholar and Garuda. The findings indicate that the nature of the philosophy of science in educational management establishes the foundational purpose and essence of educational systems, preventing them from becoming purely mechanistic. Its scope encompasses the critical evaluation of knowledge sources (epistemology), understanding the reality of organizational structures (ontology), and applying ethical and moral values in educational leadership and policy-making (axiology). Ultimately, integrating philosophical principles enables educational managers to formulate policies grounded in scientific truth and ethical considerations, navigating dynamic social and technological transformations effectively.